2020
DOI: 10.1029/2019jg005620
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Anthropogenic Impacts on pH and Aragonite Saturation State in Chesapeake Bay: Insights From a 30‐Year Model Study

Abstract: Ocean acidification (OA) is often defined as the gradual decline in pH and aragonite saturation state (ΩAr) for open ocean waters as a result of increasing atmospheric pCO2. Potential long‐term trends in pH and ΩAr in estuarine environments are often obscured by a variety of other factors, including changes in watershed land use and associated riverine carbonate chemistry and estuarine ecosystem metabolism. In this work, we investigated the anthropogenic impacts on pH and ΩAr over three decades (1986–2015) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 73 publications
6
32
0
Order By: Relevance
“…This study showed that winds can drive pH fluctuations of up to 0.3 in Chesapeake Bay over a period of a few days. These pH fluctuations are comparable to or larger than the long-term pH (0.1-0.2) decline that has been observed in Chesapeake Bay over the past three decades (Waldbusser et al, 2011;Shen et al, 2020). This adds to a growing body of evidence for large pH variability in coastal and estuarine systems (Carstensen and Duarte, 2019).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…This study showed that winds can drive pH fluctuations of up to 0.3 in Chesapeake Bay over a period of a few days. These pH fluctuations are comparable to or larger than the long-term pH (0.1-0.2) decline that has been observed in Chesapeake Bay over the past three decades (Waldbusser et al, 2011;Shen et al, 2020). This adds to a growing body of evidence for large pH variability in coastal and estuarine systems (Carstensen and Duarte, 2019).…”
Section: Discussionsupporting
confidence: 54%
“…The RCA biogeochemical model has been validated against biogeochemical data at a number of stations in Chesapeake Bay (including NO 3 , PO 4 , NH 4 , chlorophyll-a, dissolved oxygen, and organic carbon, nitrogen, and phosphorus), integrated metrics of hypoxic volume, rates of water-column primary production and respiration, and nutrient fluxes across the sediment-water surface (Brady et al, 2013;Testa et al, 2013Testa et al, , 2014Testa et al, , 2017Li et al, 2016;Ni et al, 2020). The CC model has been validated against extensive surveys of DIC, TA, and pH collected during ten cruises in 2016 (Shen et al, 2019a) and long term (1985-2015) measurements of pH at a number of monitoring stations (Shen et al, 2019b(Shen et al, , 2020. The model-predicted along-channel distribution of airsea CO 2 flux is also in good agreement with that calculated from the observational data (Shen et al, 2019a).…”
Section: Methodsmentioning
confidence: 61%
See 2 more Smart Citations
“…As excess CO 2 is absorbed into the Chesapeake Bay, it will change the pH and alkalinity of the waters resulting in acidification. Chesapeake Bay pH changes are likely to be spatially dependent; model simulations of the Chesapeake Bay found that pH increased in the upper Bay, decreased in the lower Bay, and was variable in the mid-Bay from 1986 to 2015 (Shen et al 2020).These changes to water chemistry are expected to affect the physiology of many important Chesapeake Bay marine organisms. However, there is a general lack of information on the effects of acidification on disease susceptibility of estuarine organisms.…”
Section: Ocean Acidificationmentioning
confidence: 99%